Strategic Management dan Strategic Leadership: Dua Sisi Mata Uang Kemampuan untuk Hadapi Tantangan Perubahan Lingkungan yang Drastis - Son Wandrial (Bina Nusantara University, 2011)
Management strategy and strategic leadership are like two sides of a coin that can not be separated, the management strategy is the tool in making a strategic plan for the future, while on the other hand, leadership (leadership) is more emphasis on people who have in the organization (leader and follower behavior) that will run (implementation) the formulated plan so that the goals (objectives) of the company could be reached. In a moving-forward environment, a leader is charged to be always monitoring and watching all changes. Any kind of changes will affect objective approach. A leader will not only be charged to see future, create a road map from the organization, but also has behave in manner to support the goal.